1997
DOI: 10.1007/s004380050601
|View full text |Cite
|
Sign up to set email alerts
|

Controls of the expression of aspA, the aspartyl protease gene from Penicillium roqueforti

Abstract: The gene (aspA) encoding the extracellular aspartyl protease from Penicillium roqueforti was cloned and characterized. Northern hybridization analyses and beta-casein degradation assays revealed that aspA was strongly induced by casein in the medium and efficiently repressed by ammonia. External alkaline pH overrides casein induction, resulting in aspA repression. Cis-acting motifs known to mediate nitrogen and pH regulation of fungal gene expression are present in the aspA promoter and protein-DNA binding exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…The results are consistent with the presence of potential sites for nitrogen (AreA) and pH (PacC) control described in Aspergillus and other filamentous fungi (Espeso et al, 1993) that are also found in the papA promoter, but the lack of potential CreA sites suggests carbon regulation may take place by a system different from CreA, as has been suggested in other fungi (Espeso et al, 1993 ;Ronne, 1995). Other protease genes are also repressed by glucose and ammonia, such as pepA from A. niger (Berka et al, 1990), and\or induced by peptidic nitrogen sources (casein), such as the aspA protease gene from Penicillium roqueforti (Gente et al, 1997). In this study basic and acidic pHs completely repressed papA gene expression, even in the presence of casein (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…The results are consistent with the presence of potential sites for nitrogen (AreA) and pH (PacC) control described in Aspergillus and other filamentous fungi (Espeso et al, 1993) that are also found in the papA promoter, but the lack of potential CreA sites suggests carbon regulation may take place by a system different from CreA, as has been suggested in other fungi (Espeso et al, 1993 ;Ronne, 1995). Other protease genes are also repressed by glucose and ammonia, such as pepA from A. niger (Berka et al, 1990), and\or induced by peptidic nitrogen sources (casein), such as the aspA protease gene from Penicillium roqueforti (Gente et al, 1997). In this study basic and acidic pHs completely repressed papA gene expression, even in the presence of casein (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…sclerotiorum and investigated its pattern of expression. Previous studies have shown that expression of aspartyl-and metallo-proteases is regulated in response to environmental signals (Jarai & Buxton, 1994 ;Hensel et al, 1995 ;Gente et al, 1997 ;St Leger et al, 1997). It was of interest to determine the factors which influence, in vitro, the expression of the acp1 gene to relate these to the environmental conditions encountered in planta by the fungus during symptom development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, synthesis of the acidic ACP1 is prevented at neutral or alkaline pH values at which the enzyme is inactive. pH regulation is an adaptive response for the production of secreted enzymes at their optimal pH of activity (Jarai & Buxton, 1994 ;Gente et al, 1997). In A. nidulans, the PacC transcription factor has been shown to activate transcription of alkaline genes and to repress transcription of acidic genes (Tilburn et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In general, animal rennins are not sufficient to cover world demands, and this fact has prompted research into both microbial and recombinant rennins. Although a variety of bacteria, yeasts, and fungi have been isolated as natural producers of milk-coagulating enzymes (3,10,13,26,32,45), only two genera are used worldwide in cheese production: Mucor (12, 39) and Endothia (8, 15). Several aspartic protease genes from molds and bacteria have been cloned and expressed (15,22,33,44).…”
mentioning
confidence: 99%